learning medium, mathematics, english - Kusumaningrum, Yulinda; Ellyawati, Hetty Catur; Rifa'i, Ahmad (Universitas Semarang, 2022)
Elementary school (SD) is the most basic level of formal education in Indonesia. Students in elementary schools are students who are not only classified in the concrete operation stage but also children at the age of playing, so that some subjects still require material explanation from a teacher. In delivering the material requires a media as a means to transmit messages from sender to recipient of the message. Mathematics is a subject that requires media in delivering its material. Abstract mathematical concepts make it difficult for students to understand the material, especially mathematics combined with English in its delivery, so it is very important media in learning. This is the background of the community service team to provide training in making English-based mathematics learning media for teachers at SD IT Al Mawadah Semarang. This activity was held at SD IT AL Mawadah Semarang by lecturing method and hands-on practice. There were 13 participants in this training, all of whom were elementary school teachers in grades one to three. The activity lasts for 1 day with a duration of 3 hours.The training on making English-based mathematics learning media has a positive impact for teachers at SD IT Al Mawadah Semarang. So that the media can be used for offline and online learning